Functional characterization of a cucumber (cucumis sativus L.) vacuolar invertase, CsVI1, involved in hexose accumulation and response to low temperature stress - Feng, Ziliu; Zheng, Fenghua; Wu, Silin; Li, Rui; Li, Yue; Zhong, Jiaxin; Zhao, Hongbo (International journal of molecular sciences, 2021)
Cucumber (Cucumis sativus L.), an important vegetable plant species, is susceptible to low temperature stress especially during the seedling stage. Vacuolar invertase (VI) plays important roles in plant responses to abiotic stress. However, the molecular and biochemical mechanisms of VI function in cucumber, have not yet been completely understood and VI responses to low temperature stress and it functions in cold tolerance in cucumber seedlings are also in need of exploration. The present study found that hexose accumulation in the roots of cucumber seedlings under low temperature stress is closely related to the observed enhancement of invertase activity. Our genome-wide search for the vacuolar invertase (VI) genes in cucumber identified the candidate VI-encoding gene CsVI1. Expression profiling of CsVI1 showed that it was mainly expressed in the young roots of cucumber seedlings. In addition, transcriptional analysis indicated that CsVI1 expression could respond to low temperature stress. Recombinant CsVI1 proteins purified from Pichia pastoris and Nicotiana benthamiana leaves could hydrolyze sucrose into hexoses. Further, overexpression of CsVI1 in cucumber plants could increase their hexose contents and improve their low temperature tolerance. Lastly, a putative cucumber invertase inhibitor was found could form a complex with CsVI1. In summary, these results confirmed that CsVI1 functions as an acid invertase involved in hexose accumulation and responds to low temperature stress in cucumber seedlings.